The Influence of Investment Knowledge, Risk Perception, and Return Expectations on Stock Investment Interest Among University Students. - Anwar, Adrianda; Rahayu, Nila; Pradnyani, I Gusti Agung Arista; Genadi, Yeldy Dwi (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
Technological advancements have contributed to the growing participation of the younger generation in stock market investment. This study aims to examine the influence of investment knowledge, risk perception, and return expectations on stock investment interest among students of the Faculty of Economics and Business at the University of Mataram. The research employs a quantitative approach using a survey method. The sample consists of 93 fourth-semester students selected through purposive sampling. Data were analyzed using multiple linear regression with the aid of SPSS software. The results indicate that all three independent variables—investment knowledge, risk perception, and return expectations—have a positive and significant influence on stock investment interest, both simultaneously and partially. Among these, return expectations represent the most dominant factor in shaping investment interest. This study underscores the importance of comprehensive investment literacy in fostering healthy and sustainable investment behavior among the younger generation.